2017
DOI: 10.1175/jas-d-16-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Global Circuit Variations from Vostok and Concordia Electric Field Measurements

Abstract: Atmospheric electric field measurements from the Concordia station on the Antarctic Plateau are compared with those from Vostok (560 km away) for the period of overlap and to Carnegie (1915-29) and extended Vostok (2006-11) measurements. The Antarctic data are sorted according to several sets of criteria for rejecting local variability to examine a local summer-noon influence on the measurements and to improve estimates of the global signal. The contribution of the solar wind influence is evaluated and remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
35
0
3
Order By: Relevance
“…However, even after this transformation the main maximum of the simulated IP variation would be reached about 2 hr earlier than that of the Carnegie curve. What is more important, this could not explain the conspicuous difference of amplitudes corresponding to winter (NDJ and FMA) and summer (MJJ and ASO), clearly visible in the results of simulations but absent in the Carnegie data (see Figures c–f and Table ) and in the data from other measurement campaigns (e.g., Burns et al, ; Figure 8). In addition, the whole idea of simply reducing the contribution of oceans lacks thorough substantiation on the basis of precise physical criteria; note that Mach et al () found that oceanic thunderstorms and ESCs actually produce greater mean currents than their land counterparts, although, strictly speaking, it would be more natural to compare current densities rather than total currents supplied by clouds.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…However, even after this transformation the main maximum of the simulated IP variation would be reached about 2 hr earlier than that of the Carnegie curve. What is more important, this could not explain the conspicuous difference of amplitudes corresponding to winter (NDJ and FMA) and summer (MJJ and ASO), clearly visible in the results of simulations but absent in the Carnegie data (see Figures c–f and Table ) and in the data from other measurement campaigns (e.g., Burns et al, ; Figure 8). In addition, the whole idea of simply reducing the contribution of oceans lacks thorough substantiation on the basis of precise physical criteria; note that Mach et al () found that oceanic thunderstorms and ESCs actually produce greater mean currents than their land counterparts, although, strictly speaking, it would be more natural to compare current densities rather than total currents supplied by clouds.…”
Section: Resultsmentioning
confidence: 81%
“…Adapted from Slyunyaev et al (). (c)–(f) Comparison of the simulated diurnal variations of the IP corresponding to different seasons (A, blue) with the corresponding fits to the Carnegie data given by Harrison () (B, red) and Burns et al () (C, green). In panels (a) and (b) the IP is presented as a fraction of the annual mean; in panels (c)–(f) the IP is shown as a fraction of the respective seasonal mean.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These ships recorded the average fair‐weather electric field as a function of Universal Time during their voyages across the world's oceans to establish the diurnal variation of the GEC [ Whipple , ]. The resulting annual average variation given by Israel [, Appendix, Table XIX] is known as the "classic" Carnegie curve, and provides a climatology that approximates the modern measurements of the fair weather electric field in the Antarctic [ Burns et al , , , ] and the ionospheric potential [ Markson , ]. The Carnegie curve's early 20 th century origins make it a natural reference point against which to assess large‐scale changes in electrified weather with the passage of time [ Harrison , ].…”
Section: Introductionmentioning
confidence: 99%